DEVELOPMENT OF WORKSHEETS BASED ON THE EXTRACTION OF STEVIOSIDE FROM STEVIA LEAVES (STEVIA REBAUDIANA) AS A SHEET FOR THE MAKING OF LEMON LEMONGRASS INSTANT BEVERAGES - Tanti Herdianty; Neneng Windayani; Sari Sari (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to analyze the validation results and describe the appearance of the worksheet on stevioside extraction from stevia leaves. The method used in this research is Design-Based Research (DBR) with the ADDIE model. The project-based worksheet display contains questions based on the stages of project-based learning, including the stage of analyzing problems, designing projects, conducting experiments, compiling drafts/prototypes, product assessment, and finalizing and publishing products on stevioside extraction from stevia leaves (stevia rebaudiana) as lemongrass instant drink sweetener. The worksheets are validated by three validators, namely material experts and media experts. The results of the project-based worksheet validation test on stevioside extraction as a sweetener were declared valid with an average value of 0.85 including the high category, meaning that the worksheets can be used as a medium for supporting learning activities in the laboratory in addictive and additive chemistry courses.